A prospective study of the importance of enteric fever as a cause of non-malarial febrile illness in patients admitted to Chittagong Medical College Hospital, Bangladesh. Issue 1 (December 2016) - Maude, Rapeephan; Ghose, Aniruddha; Samad, Rasheda; de Jong, Hanna; Fukushima, Masako; Wijedoru, Lalith; Hassan, Mahtab; Hossain, Md; Karim, Md; Sayeed, Abdullah; van den Ende, Stannie; Pal, Sujat; et al.
Abstract Background Fever is a common cause of hospital admission in Bangladesh but causative agents, other than malaria, are not routinely investigated. Enteric fever is thought to be common. Methods Adults and children admitted to Chittagong Medical College Hospital with a temperature of ≥38.0 °C were investigated using a blood smear for malaria, a blood culture, real-time PCR to detectSalmonella Typhi, S. Paratyphi A and other pathogens in blood and CSF and an NS1 antigen dengue ELISA. Results We enrolled 300 febrile patients with a negative malaria smear between January and June 2012: 156 children (aged ≤15 years) and 144 adults with a median (interquartile range) age of 13 (5–31) years and median (IQR) illness duration before admission of five (2–8) days. Clinical enteric fever was diagnosed in 52 patients (17.3 %), lower respiratory tract infection in 48 (16.0 %), non-specific febrile illness in 48 (16.0 %), a CNS infection in 37 patients (12.3 %), urinary sepsis in 23 patients (7.7 %), an upper respiratory tract infection in 21 patients (7.0 %), and diarrhea or dysentery in 21 patients (7.0 %). Malaria was still suspected in seven patients despite a negative microscopy test.S. Typhi was detected in blood by culture or PCR in 34 (11.3 %) of patients. Of noteRickettsia typhi andOrientia tsutsugamushi were detected by PCR in two and one patient respectively. Twenty-nine (9 %) patients died during their hospital admission (15/160 (9.4 %) of children and 14/144 (9.7 %) adults). Two of 52 (3.8 %) patients with enteric fever, 5/48 (10.4 %) patients with lower respiratory tract infections, and 12/37 (32.4 %) patients with CNS infection died. Conclusion Enteric fever was confirmed in 11.3 % of patients admitted to this hospital in Bangladesh with non-malaria fever. Lower respiratory tract and CNS infections were also common. CNS infections in this location merit more detailed study due to the high mortality.